Good's Syndrome Patients Hospitalized for Infections: A Single-Center Retrospective Study. Issue 47 (November 2015) - Sun, Xuefeng; Shi, Juhong; Wang, Mengzhao; Xu, Kaifeng; Xiao, Yi
Abstract : Abstract: Good's syndrome (GS) is a rare combination of thymoma and hypogammaglobulinemia, resulting in immunodeficiency. Patients with GS are highly susceptible to bacterial infection, particularly encapsulated bacterial infection in upper and lower respiratory tracts. Good's syndrome patients with moderate-to- severe infection are often hospitalized. Clinical features of GS patients remain to be characterized. Patients with the discharge diagnosis of GS and simultaneous infection from Peking Union Medical College Hospital between January 2001 and July 2015 were retrospectively analyzed. Among 14 hospitalized GS patients, 12 of them were admitted for severe infections. Mean patient age was 56.7 + 10.1 years. Average concentrations of serum IgG, IgA, and IgM were 2.3 + 1.9 g/L, 0.28 + 0.28 g/L, and 0.06 + 0.07 g/L, respectively. Respiratory and intestinal tracts were the most common sites for infection, which occurred in 7 and 4 patients, respectively. Pathogens identified in 10 patients included cytomegalovirus in 5 patients, Pneumocystis jirovecii, Clostridium difficile in 2 patients, Klebsiella pneumonia in 2 patients, and Streptococcus pneumonia and Hemophilus influenza in 1 patient. Ten patients were treated with antibiotics and immunoglobulin replacement. Only 1 patient who was on immunosuppressant therapy died from P. jirovecii pneumonia. Infection was the most frequent cause for hospitalization of GS patients. Both respiratory and intestinal tracts were the most common sites of infection. Cytomegalovirus and P. jirovecii represented 2 common opportunistic pathogens isolated from hospitalized GS patients with infections.